EFEKTIVITAS PELATIHAN â€œPEDEâ€ (PEMAAFAN, EFIKASI DIRI, DAN EMPATI) UNTUK MENINGKATKAN SCHOOL WELL-BEING SISWA - Setyawan, Imam; Dewi, Endah Kumala (Faculty of Psychology, Diponegoro University, 2019)
This study aims to examine the effectiveness of PEDE training (Forgiveness, Self-Efficacy, and Empathy) to increase school well-being of students. The experimental design of this study was pretest-posttest without control group design. Participants were 50 students from vocational high schools, 21 man and 29 woman. Data were collected using School Well-Being Scale (20 items; Î± = .81). Data were analyzed using paired sample t-test to determine the differences in the level of school well-being before and after treatment. The results of the analysis showed a significant increase in school well-being (t (49)= 3.904; p <.001) from pretest (M= 60.98; SD= 4.162) to posttest (M= 63.28; SD=4.291). PEDE training (Forgiveness, Self-Efficacy, and Empathy) is proven to increase school well-being of students. Forgiveness is needed by students in facing the weaknesses and pressures they feel at school, pressure can come from within themselves, other people and the environment. Student satisfaction is inseparable from empathy, where students are able to understand and relate to cognitive and affective experiences from the perspective of others. With the various pressures and challenges faced, students need the self-efficacy to be able to succeed in achieving each of their goals, so that they receive recognition and appreciation in the school environment.